ASSOCIATION OF RISK AND PROTECTIVE FACTORS WITH THE MENTAL HEALTH STATUS AMONG ADOLESCENTS IN PUNJAB, PAKISTAN - Nasim Akhtar; Farah Nazir; Asma Batool (International Journal of Contemporary Issues in Social Sciences, 2024)
A person is born with risk factors that could become stress or protective factors that could compromise their mental health. This study should investigate how risk factors-such as peer pressure, anxiety, stress, emotional problems, behavioral problems, hyperactivity, and bullying-and protective factors-such as prosocial conduct, family relationships, and self-esteem-affect teenagers' mental health. In District Lahore, 240 high school students participated in this cross-sectional survey. Questionnaires were given to participants to complete as part of the study instrument. Smart PLS and SPSS 23.0 were used to evaluate the data that was gathered. The results showed that the protective factor and mental health status had been significantly and negatively impacted by the risk factor. Additionally, statistical analysis revealed that the protective factor had a good and significant impact on the state of mental health. The impact of the risk factor on the mental health status was also significantly mediated by the protective factor. In order to preserve teenagers' mental health, the risk factor must be avoided and the protective factor must be strengthened.